Navigating Existential Literacy in the Age of Anxiety: A Failosophical Critique of Overthinking and the Crisis of Digital Citizenship - Andri Fransiskus Gultom (Actual Insight, 2025)
This study aims to examine the phenomenon of overthinking (OVT) among Generation Z in Indonesia through the lenses of